2015
DOI: 10.1186/s12909-015-0501-4
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning in resource-poor settings: lessons from a medical school in Ghana

Abstract: Problem-based learning (PBL) is arguably one of the most important innovations in medical education in the last century. The evident benefits of PBL and the changing face of medicine and medical education have led many institutions including those in resource-poor settings to consider the adoption of PBL curricula. However, experts are uncertain about how successful PBL will be in such settings, as literature on the implementation of PBL in resource-poor settings appears to be inadequate. The University of Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 24 publications
(26 reference statements)
3
50
0
Order By: Relevance
“…Problem-based learning (PBL), where students solve clinical problems as a group, improves knowledge, critical reasoning and social skills 22. However, PBL research outside HICs is rare 23. Telemedicine offers one way to overcome the infrastructure requirements that limit face-to-face PBL18 but is underused in global mental health 24…”
Section: Introductionmentioning
confidence: 99%
“…Problem-based learning (PBL), where students solve clinical problems as a group, improves knowledge, critical reasoning and social skills 22. However, PBL research outside HICs is rare 23. Telemedicine offers one way to overcome the infrastructure requirements that limit face-to-face PBL18 but is underused in global mental health 24…”
Section: Introductionmentioning
confidence: 99%
“…Problem-based learning (PBL) structured medical education has been used by North American medical schools for more than 60 years but has only been introduced to other global medical schools within the last 20 years [1]. Now, PBL is used in medical schools all over the world and it ‘appears to have become the preferred pedagogical strategy in tertiary education worldwide’ [2]. Research into problem-based learning compared with traditional curricula has revealed no difference in knowledge levels between programmes.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Such reforms include student-centred learning, interprofessional education, community-based education, competency-based education, e-learning and service-learning. [5,6] To implement these reforms, faculty in health professions training institutions not only need to improve the existing training methods, but also innovate other feasible methods to improve training by means of evidence-based scholarly approaches. AJHPE has had a strong tradition of publishing scholarly original research and reviews related to improving the training and performance of health professionals, using evidence-based practices.…”
mentioning
confidence: 99%